A comparison of raspberry freezing-damage during preservation in isochoric and isobaric conditions - Câmpean, Ștefan Ioan; Beșchea, George Andrei; Vuțoiu, Beatrice Georgiana; Tăbăcaru, Maria Bianca; Năstase, Gabriel (Frontiers in Nutrition, 2024)
Fruits are perishable, thus it's crucial to have an efficient preservation technique that can increase storage time while keeping physical quality and nutritional attributes in order to avoid wastage. The majority of methods for long-term storage require refrigeration. In this investigation, we assess the viability of isochoric freezing as a different technique of raspberry (Rubus idaeus L.) preservation. Raspberries were subjected to different storage conditions: isochoric freezing at -4°C, conventional isobaric settings at +3°C (refrigerator), -21°C (freezer), and -4°C with a trehalose solution in a plastic bag. The study assessed changes in weight loss, visual appearance, color, hardness, °Brix values, and pH over a seven-day period. Key findings reveal that raspberries subjected to isochoric freezing below the freezing point of water experienced minimal weight loss after seven days. Visual appearance, color, hardness, °Brix values, and pH were comparable to fresh raspberries, indicating minimal alteration. These results suggest that isochoric freezing shows potential as a preservation method that maintains the physical and chemical properties of raspberries similar to fresh fruit. Implementing diverse preservation techniques tailored to raspberries may contribute to environmental sustainability by reducing food wastage and the associated environmental impact.